Preparation method and application of self-supporting metal polyphenol network nano-film
Through interface assembly reaction, the thickness and pore size of metal polyphenol network nanofilms are regulated at the water-oil interface, and the problem of difficult nanofilms in the prior art is solved, and the preparation of self-supported nanofilms is realized, which improves separation performance and is suitable for Various separation scenarios.
Patent Information
- Application Number
- CN202411490038.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2024-12-20
AI Technical Summary
In the prior art, the thickness and pore size of the nano film are difficult to regulate, and a porous substrate is required, resulting in the separation performance of the composite film being affected by the structure and properties of the substrate itself.
Using interface assembly reaction, the metal salt is dissolved in organic solvents and polyphenols are dissolved in water. By controlling the diffusion and reaction conditions of the monomer, the coordination assembly is carried out at the water-oil interface to regulate the thickness and pore size of the film to obtain self-supported Nanofilms can be transferred to any substrate for application.
It realizes precise regulation of nanofilm thickness and pore size, improves separation performance, is suitable for accurate separation of organic small molecules, and can be transferred to different substrates, and is suitable for a variety of separation scenarios.
Smart Images

Figure CN119158422A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of membrane technology, and in particular relates to a preparation method and application of a self-supporting metal polyphenol network nano film. Background Art
[0002] Membrane separation technology is an emerging technology that uses separation membranes as its core and utilizes the membrane's efficient selective permeability to separate, purify and concentrate different components of a liquid feed. Compared with traditional separation technologies, it has the characteristics of high separation efficiency, good selectivity, low energy consumption and a wide range of applications. Currently, the hottest and most challenging area in the membrane separation field is the preparation of ultra-thin uniformly porous membranes with nanoscale pores in order to achieve higher water flux and better separation accuracy.
[0003] The metal polyphenol network is constructed by the rapid assembly of natural plant polyphenols and transition metal ions in one step. Polyphenols have universal adhesion due to their rich phenolic hydroxyl groups, and have a suitable theoretical pore size (0.2-0.8 nm). However, the rapid assembly of polyphenols and metal ions leads to uncontrollable dynamics, which in turn leads to uncontrollable thickness and pore size of the membrane, making it difficult to achieve high-precision separation. In addition, the nanofilm prepared by conventional methods needs to be supported by a porous substrate, and the separation performance of the prepared composite membrane is often affected by the polymer properties of the substrate itself. For example, patent CN104984666A discloses a metal polyphenol film and a preparation method and application thereof, wherein a metal polyphenol film is obtained by mixing a polyphenol solution and a metal salt solution and depositing them on a porous base film. Since the coordination speed of polyphenol and metal ions is extremely fast, it is difficult to achieve precise control of the film thickness and pore size. In addition, the film obtained by the co-deposition method will be affected by the structure and properties of the porous substrate itself, and the presence of the substrate will increase the mass transfer resistance, thereby affecting the separation performance of the membrane; patent CN111203107A discloses a polyphenol-iron nanofilm and a preparation method and application thereof, which controls the formation speed and structure of the separation cortex by controlling the oxidation process of ferrous ions in an aqueous solution to obtain a dense and defect-free polyphenol-iron nanofilm, and effectively controls the thickness and pore size of the separation cortex of the polyphenol-iron nanofilm by adjusting the reaction conditions, thereby controlling the separation performance of the polyphenol-iron nanofilm, but the nanofilm prepared by this method will also be restricted by the substrate, thereby affecting the separation performance of the membrane. Patent CN118767714A discloses a metal polyphenol nanofilm and its application in nanofiltration separation. The metal polyphenol nanofilm is formed on a porous support membrane by rapid assembly of metal ions in the oil phase and polyphenol ligands in the water phase at the interface. The rapid coordination of polyphenols and metal ions will lead to uncontrollable film-forming reaction kinetics, and the film thickness and pore size are difficult to accurately control, thereby affecting the separation performance of the membrane. Summary of the invention
[0004] [Technical issues]
[0005] The technical problem to be solved by the present invention is that the thickness and pore size of the nanofilm in the prior art are difficult to control and the nanofilm needs to be mounted on a porous substrate, and the separation performance of the prepared composite membrane is affected by the structure and properties of the substrate itself.
[0006] [Technical solution]
[0007] In order to solve the above problems, the present invention provides a method for preparing a self-supporting metal polyphenol network nanofilm, which mainly adopts an interfacial assembly reaction, wherein two reaction monomers are respectively dissolved in immiscible oil-water phases so that the two are coordinated and assembled at the interface and are confined to this area to form a film. The growth of the film is controlled by controlling the diffusion of the monomers, and the thickness and pore size of the film are regulated to finally obtain a self-supporting nanofilm that can be transferred to any substrate and applied to different separation scenarios.
[0008] The present invention provides a method for preparing a self-supporting metal polyphenol network nano film, comprising the following steps:
[0009] (1) dissolving a metal salt in an organic solvent to obtain a metal salt solution; dissolving polyphenol and sodium chloride in water to obtain a polyphenol aqueous solution, and adjusting the pH thereof;
[0010] (2) adding a metal salt solution into a polyphenol aqueous solution, sealing and allowing the solution to react, and obtaining a metal polyphenol network nanofilm at the water-oil interface by an interfacial assembly method.
[0011] In one embodiment of the present invention, in step (1), the metal salt is one or more of ferric acetylacetonate, aluminum acetylacetonate, copper acetylacetonate, zinc acetylacetonate, zirconium acetylacetonate, magnesium acetylacetonate, cobalt acetylacetonate, nickel acetylacetonate, manganese acetylacetonate, and chromium acetylacetonate; preferably ferric acetylacetonate.
[0012] In one embodiment of the present invention, in step (1), the organic solvent is one or more of n-hexane, toluene, petroleum ether, and dichloromethane; preferably n-hexane.
[0013] In one embodiment of the present invention, in step (1), the concentration of the metal salt solution is 0.12-0.4 mg / mL, preferably 0.2 mg / mL.
[0014] In one embodiment of the present invention, in step (1), the polyphenol is one or more of tannic acid, ellagic acid, phytic acid, catechol, and pyrogallol; preferably tannic acid.
[0015] In one embodiment of the present invention, in step (1), the concentration of polyphenol in the polyphenol aqueous solution is 2-8 mg / mL, preferably 2 mg / mL.
[0016] In one embodiment of the present invention, in step (1), the pH value of the polyphenol aqueous solution is adjusted to 3-7, preferably 3.
[0017] In one embodiment of the present invention, in step (1), the sodium chloride concentration in the polyphenol aqueous solution is 0.4-0.6 mol / L, preferably 0.4 mol / L, in order to enhance the ionic strength of the solution and prevent the polyphenols from aggregating.
[0018] In one embodiment of the present invention, in step (2), the mass ratio of the metal salt to the polyphenol is 1:1-100.
[0019] In one embodiment of the present invention, in step (2), the sealed static reaction time is 60 to 360 minutes, and the sealed static reaction temperature is 25 to 30°C. Furthermore, the sealed static reaction time is preferably 60 minutes, and the temperature is preferably 25°C.
[0020] The present invention also provides a self-supporting metal polyphenol network nano film prepared by the method.
[0021] A metal polyphenol network nano composite film consists of the self-supporting metal polyphenol network nano film and a substrate.
[0022] In one embodiment of the present invention, the substrate is one or more of polyacrylonitrile ultrafiltration membrane, polyvinylidene fluoride ultrafiltration membrane, polyvinyl chloride ultrafiltration membrane, polypropylene ultrafiltration membrane, polyether sulfone ultrafiltration membrane, cellulose acetate ultrafiltration membrane, and porous anodized aluminum membrane.
[0023] [Beneficial Effects]
[0024] (1) The present invention adopts an interfacial assembly method to grow a self-supporting metal polyphenol network nanofilm at the interface between a polyphenol aqueous solution and an organic solution of a metal salt;
[0025] (2) The present invention regulates the thickness and pore size of the self-supporting nanofilm by regulating the interface assembly time, reactant concentration, sodium chloride concentration, organic solvent type, pH value, and reaction temperature, thereby regulating the separation performance of the nanofilm;
[0026] (3) The present invention uses natural polyphenols to coordinate with transition metals to obtain a uniform and dense metal polyphenol network nanofilm with a suitable pore size (~0.4nm) suitable for precise separation of organic small molecules;
[0027] (4) The self-supporting metal polyphenol network nanofilm obtained in the present invention can be transferred to any substrate and applied in various separation scenarios due to its universal adhesion. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1This is a scanning electron microscope image of the metal polyphenol network nanofilm prepared in Example 1. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0030] The metal polyphenol network nano film prepared by the present invention is used for desalination, and the desalination rate and water flux are two important parameters for evaluating the nanofiltration performance of the nano film.
[0031] The parameters were obtained by cross-flow filtration and calculation. An inorganic salt solution with a concentration of 1g / L was used as the raw material, and the filtration test was carried out in a constant temperature water bath at 25°C and a pressure of 0.4MPa. The time required for the composite membrane to pass through 5mL, 7mL, and 10mL of permeate was recorded respectively, and the desalination rate and water flux were calculated by formula.
[0032] The calculation formula of desalination rate is:
[0033]
[0034] Among them, C f Indicates the concentration of salt ions in the aqueous solution before treatment; C p Indicates the concentration of salt ions in the aqueous solution after treatment.
[0035] The definition of water flux is: the volume of water that passes through a unit membrane area per unit time under certain operating pressure conditions, and its unit is L·m -2 ·h -1 , the calculation formula is:
[0036]
[0037] Where V is the volume of the permeated solution, in L; A is the effective membrane area, in m 2 ; t represents time, the unit is h.
[0038] Polyethylene glycol (PEG) with different molecular weights (200, 400, 600, 800, 1000) was dissolved in water to prepare different raw material solutions, and filtration tests were performed at 25°C and 0.4MPa. The water phase nanofiltration performance of the composite membrane was evaluated by recording the permeation flux of the composite membrane and measuring the raw material / filtrate concentration. Polyethylene glycol with different molecular weights was retained, and the molecular weight cut-off was the molecular weight of the polyethylene glycol with a retention rate of 90%.
[0039] The concentration of polyethylene glycol needs to be determined by potassium permanganate oxidation method. First, prepare 5mL of potassium permanganate solution with a concentration of 2mg / L, and add 0.6mL of concentrated sulfuric acid to adjust it to strong acidity. Use a pipette to transfer 15μL of potassium permanganate solution to 75μL of PEG solution, mix well and let stand for 24 hours. After oxidation is complete, dilute the above solution to 3mL, and measure its absorbance at 525nm by ultraviolet-visible spectrometer (UV-vis) to determine the concentration of PEG.
[0040] Using PEG of different molecular weights as molecular probes, the pore size and pore size distribution of the composite membrane can be obtained based on the retention of the composite membrane. The specific calculation method is as follows:
[0041] The Stokes radius (r) of PEG can be calculated by the following formula:
[0042]
[0043] Where Mw is the molecular weight of PEG.
[0044] The normal distribution of the composite membrane pore size can be calculated by the following formula:
[0045]
[0046] Where dp is the membrane pore size, in m; μp is the geometric mean diameter of PEG corresponding to a retention rate of 50%, in m; σp is the geometric standard deviation of μp, which is defined as the ratio of the geometric mean radius of PEG corresponding to a retention rate of 84.13% to the geometric mean radius of PEG corresponding to a retention rate of 50%.
[0047] The following examples further illustrate the preparation method of the self-supporting metal polyphenol nanofilm and its nanofiltration separation performance.
[0048] Example 1
[0049] (1) Weigh 0.06 g of tannic acid and 0.70 g of sodium chloride and dissolve them in 30 mL of ultrapure water to obtain a polyphenol aqueous solution with a polyphenol concentration of 2 mg / mL, and adjust the pH to 3 with a 1 mol / L hydrochloric acid aqueous solution; weigh 0.006 g of ferric acetylacetonate and dissolve it in 30 mL of n-hexane to obtain a ferric acetylacetonate solution with a concentration of 0.2 mg / mL.
[0050] (2) slowly adding the ferric acetylacetonate solution obtained in step (1) into the polyphenol aqueous solution, sealing and standing the mixture at 25° C. for 60 minutes to obtain a self-supporting metal polyphenol network nanofilm at the oil-water interface.
[0051] Depend on Figure 1As shown, a film morphology with metal polyphenol network nanoprotrusions on the surface appeared, indicating the successful preparation of the metal polyphenol network nanofilm.
[0052] Embodiments 2 to 4
[0053] The interface assembly time was adjusted to 120, 240, and 360 min, respectively. The other conditions were the same as in Example 1, and a metal polyphenol network nanofilm was obtained. The details are shown in Table 1.
[0054] Comparative Examples 1 to 3
[0055] The interface assembly time was adjusted to 5, 10, and 30 min, respectively, and the other conditions were the same as in Example 1, to obtain a metal polyphenol network nanofilm, as shown in Table 1.
[0056] The thickness and pore size of the metal polyphenol network nanofilms prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were tested. The results are shown in Table 1.
[0057] Table 1 Thickness and pore size of metal polyphenol network nanofilms prepared in Examples 1 to 4 and Comparative Examples 1 to 3
[0058] test Comparative Example 1 Comparative Example 2 Comparative Example 3 Example 1 Example 2 Example 3 Example 4 Time (min) 5 10 30 60 120 240 360 Thickness(nm) 6 11 14 25 32 35 36 Pore size (nm) 0.96 0.78 0.58 0.40 0.39 0.42 0.38
[0059] From the data in Table 1, it can be seen that with the extension of the interface assembly time, the thickness of the obtained metal polyphenol network nanofilm increases rapidly and the pore size decreases rapidly within 0 to 60 minutes. After 60 minutes, the film thickness and pore size are basically stable, indicating that the metal polyphenol coordination film formation is basically completed.
[0060] Embodiment 5-6
[0061] The concentrations of tannic acid in the polyphenol aqueous solution were adjusted to 4 and 8 mg / mL (as shown in Table 2), respectively, and the other conditions were the same as those in Example 1 to obtain a metal polyphenol network nanofilm.
[0062] Comparative Examples 4 to 6
[0063] The concentrations of tannic acid in the polyphenol aqueous solution were adjusted to 0.2, 0.4, and 1.2 mg / mL (as shown in Table 2), respectively, and the other conditions were the same as in Example 1 to obtain a metal polyphenol network nanofilm.
[0064] The metal polyphenol network nanofilms prepared in Examples 5 to 6 and Comparative Examples 4 to 6 were tested. The results are shown in Table 2.
[0065] Table 2 Thickness and pore size of metal polyphenol network nanofilms prepared in Examples 5 to 6 and Comparative Examples 4 to 6
[0066]
[0067] From the data in Table 2, it can be seen that with the increase of tannic acid concentration, the thickness of the metal polyphenol network nanofilm gradually increases and the pore size gradually decreases. When the tannic acid concentration is low, it is not enough to form a dense film; when the tannic acid concentration reaches 2 mg / mL, sufficient tannic acid coordinates with iron ions to form a smooth and dense nanofilm; excessive tannic acid will cause the metal polyphenol complex to aggregate on the membrane surface and increase the roughness.
[0068] Embodiment 7-8
[0069] The concentrations of ferric acetylacetonate in the organic metal salt solution were adjusted to 0.12 and 0.4 mg / mL (as shown in Table 3), respectively, and the other conditions were the same as those in Example 1 to obtain a metal polyphenol network nanofilm.
[0070] Comparative Examples 7 to 9
[0071] The concentrations of ferric acetylacetonate in the organic metal salt solution were adjusted to 0.02, 0.04, and 0.8 mg / mL (as shown in Table 3), respectively. The other conditions were the same as those in Example 1, and a metal polyphenol network nanofilm was obtained.
[0072] The metal polyphenol network nanofilms prepared in Examples 7 to 8 and Comparative Examples 7 to 9 were tested. The results are shown in Table 3.
[0073] Table 3 Thickness and pore size of metal polyphenol network nanofilms prepared in Examples 7 to 8 and Comparative Examples 7 to 9
[0074]
[0075] It can be seen from the data in Table 3 that as the concentration of ferric acetylacetonate increases, the thickness of the metal polyphenol network nanofilm gradually increases and the pore size gradually decreases. When the iron concentration is low, it is not enough to form a dense film; when the iron concentration is high, because the chelating sites provided by tannic acid are limited, excessive iron will destroy the metal polyphenol network structure and cause defects, making the pore size larger.
[0076] Example 9
[0077] The concentration of sodium chloride in the polyphenol aqueous solution was adjusted to 0.6 mol / L (as shown in Table 4), and the other conditions were the same as in Example 1 to obtain a metal polyphenol network nanofilm.
[0078] Comparative Examples 10 to 14
[0079] The concentration of sodium chloride in the polyphenol aqueous solution was adjusted to 0, 0.1, 0.2, 0.8, and 2 mol / L (as shown in Table 4), and the other conditions were the same as in Example 1 to obtain a metal polyphenol network nanofilm.
[0080] The metal polyphenol network nanofilms prepared in Example 9 and Comparative Examples 10 to 14 were tested. The results are shown in Table 4.
[0081] Table 4 Thickness and pore size of metal polyphenol network nanofilms prepared in Example 9 and Comparative Examples 10 to 14
[0082]
[0083] From the data in Table 4, it can be seen that with the increase of sodium chloride concentration in the polyphenol aqueous solution, the thickness of the nanofilm first increases and then decreases, and the pore size first decreases and then increases. This is because when the sodium chloride concentration is low, the solution ionic strength is low, which easily leads to the aggregation of tannic acid, and the reduction of binding sites with trivalent iron, resulting in defects in the film; when the sodium chloride concentration is high, the solution ionic strength is strong, which weakens the intermolecular interaction force, weakens the binding of polyphenols with metal ions, and thus leads to a decrease in film thickness and an increase in pore size.
[0084] Embodiments 10 to 12
[0085] The type of organic solvent was changed (as shown in Table 5), and the other conditions were the same as in Example 1 to obtain a metal polyphenol network nanofilm.
[0086] The metal polyphenol network nanofilms prepared in Examples 10 to 12 were tested. The results are shown in Table 5.
[0087] Table 5 Thickness and pore size of metal polyphenol network nanofilms prepared in Examples 10 to 12
[0088]
[0089] From the data in Table 5, it can be seen that the thickness of the nanofilm is positively correlated with the interfacial tension of the organic solvent, and the pore size of the nanofilm is negatively correlated with the interfacial tension of the organic solvent. This is because the interfacial tension will affect the diffusion of metal ions. As the interfacial tension increases, the diffusion rate of metal ions increases, and polyphenols coordinate with more metal ions, which increases the film thickness and reduces the pore size.
[0090] Embodiments 13-14
[0091] The pH values of the polyphenol aqueous solution were adjusted to 5 and 7 respectively (as shown in Table 6), and the other conditions were the same as in Example 1 to obtain a metal polyphenol network nanofilm.
[0092] Comparative Examples 15 to 18
[0093] The pH values of the polyphenol aqueous solution were adjusted to 1, 9, 11, and 13 (as shown in Table 6), respectively, and the other conditions were the same as in Example 1 to obtain a metal polyphenol network nanofilm.
[0094] The metal polyphenol network nanofilms prepared in Examples 13 to 14 and Comparative Examples 15 to 18 were tested. The results are shown in Table 6.
[0095] Table 6 Thickness and pore size of metal polyphenol network nanofilms prepared in Examples 13 - 14 and Comparative Examples 15 - 18
[0096]
[0097] As can be seen from the data in Table 6, when 1 < pH < 7, as the pH value increases, the thickness of the nanofilm first increases and then decreases, and the pore size first decreases and then increases. This is because the metal polyphenol network has pH dependence; when pH > 7, part of tannic acid is oxidized to quinone structure or undergoes hydrolysis, resulting in an increase in steric hindrance and making it difficult to coordinate with ferric ions, so the formed film is relatively loose and thick; when pH = 13, part of the iron ions are prone to form iron hydroxide precipitation, resulting in a decrease in the concentration of iron acetylacetonate, and defects appear in the formed nanofilm.
[0098] Example 15
[0099] The interfacial reaction temperature was changed to 30 °C (as shown in Table 7), and the other conditions were the same as in Example 1 to obtain a metal polyphenol network nanofilm.
[0100] Comparative Examples 19 - 21
[0101] The interfacial reaction temperature was changed to 40, 50, 60 °C (as shown in Table 7), and the other conditions were the same as in Example 1 to obtain metal polyphenol network nanofilms.
[0102] The metal polyphenol network nanofilms prepared in Example 15 and Comparative Examples 19 - 21 were tested. The results are shown in Table 7.
[0103] Table 7 Thickness and pore size of metal polyphenol network nanofilms prepared in Example 15 and Comparative Examples 19 - 21
[0104] test Example 1 Embodiment 15 Comparative Example 19 Comparative Example 20 Comparative Example 21 Temperature(℃) 25 30 40 50 60 Thickness(nm) 25 19 17 15 16 Pore size (nm) 0.40 0.54 0.63 0.82 0.69
[0105] As can be seen from the data in Table 7, as the interfacial assembly reaction temperature increases, the film thickness gradually becomes thinner and the pore size gradually becomes larger. This is because the increase in temperature will cause the "interfacial boiling" phenomenon, resulting in an unstable interface, making the formed film thinner and prone to defects.
[0106] Comparative Example 22
[0107] Tannic acid and sodium chloride were dissolved in n - hexane, and iron acetylacetonate was dissolved in water. The other conditions were the same as in Example 1, and interfacial assembly into a film could not be carried out.
[0108] The self - supporting nanofilm prepared in Example 1 was fished out with a wire loop and transferred to different substrates to obtain a metal polyphenol network nanocomposite film. The prepared metal polyphenol network nanocomposite film was tested. The results are shown in Table 8.
[0109] Table 8 Water flux and retention rate of metal polyphenol network nanocomposite membrane
[0110]
[0111] It can be seen from the data in Table 8 that the self-supporting metal polyphenol network nanofilm can be transferred to a variety of substrates to form a composite membrane, and because the rich phenolic hydroxyl groups of tannic acid give it good adhesion to the substrate, a dense and smooth separation layer can be formed on the substrate. The various composite membranes prepared have good water flux and retention performance for nanofiltration tests.
[0112] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a self-supporting metal polyphenol network nanofilm, It is characterized in that The steps include: (1) dissolving a metal salt in an organic solvent to obtain a metal salt solution; dissolving polyphenol and sodium chloride in water to obtain a polyphenol aqueous solution, and adjusting the pH of the polyphenol aqueous solution; (2) Adding the metal salt solution to the polyphenol aqueous solution, sealing and allowing to react, and growing a thin film at the interface between the polyphenol aqueous solution and the metal salt solution, namely, a self-supporting metal polyphenol network nanofilm.
2. A method for preparing a self-supporting metal polyphenol network nanofilm according to claim 1, It is characterized in that In step (1), the polyphenol is one or more of tannic acid, ellagic acid, phytic acid, catechol, and pyrogallol; the metal salt is one or more of ferric acetylacetonate, aluminum acetylacetonate, copper acetylacetonate, zinc acetylacetonate, zirconium acetylacetonate, magnesium acetylacetonate, cobalt acetylacetonate, nickel acetylacetonate, manganese acetylacetonate, and chromium acetylacetonate; and the organic solvent is one or more of n-hexane, toluene, petroleum ether, and dichloromethane.
3. The method for preparing a self-supporting metal polyphenol network nanofilm according to claim 1, It is characterized in that In step (1), the concentration of polyphenol in the polyphenol aqueous solution is 2-8 mg / mL; the concentration of sodium chloride in the polyphenol aqueous solution is 0.4-0.6 mol / L.
4. The method for preparing a self-supporting metal polyphenol network nanofilm according to claim 1, It is characterized in that In step (1), the concentration of the metal salt solution is 0.12 to 0.4 mg / mL.
5. The method for preparing a self-supporting metal polyphenol network nanofilm according to claim 1, It is characterized in that In step (1), the pH value of the polyphenol aqueous solution is adjusted to 3-7.
6. The method for preparing a self-supporting metal polyphenol network nanofilm according to claim 1, It is characterized in that In step (2), the mass ratio of the metal salt to the polyphenol is 1:1-100.
7. The method for preparing a self-supporting metal polyphenol network nanofilm according to claim 1, It is characterized in that In step (2), the sealed static reaction time is 60 to 360 minutes, and the sealed static reaction temperature is 25 to 30°C.
8. The self-supporting metal polyphenol network nanofilm prepared by the method according to any one of claims 1 to 7.
9. A metal polyphenol network nanocomposite film, It is characterized in that It consists of the self-supporting metal polyphenol network nano film as described in claim 8 and a substrate.
10. The metal polyphenol network nanocomposite film according to claim 9, It is characterized in that The substrate is one or more of polyacrylonitrile ultrafiltration membrane, polyvinylidene fluoride ultrafiltration membrane, polyvinyl chloride ultrafiltration membrane, polypropylene ultrafiltration membrane, polyether sulfone ultrafiltration membrane, cellulose acetate ultrafiltration membrane, and porous anodized aluminum membrane.
Citation Information
Cited By
BiOCl / TiO2 composite film with amphiphilic surface as well as preparation method and application of BiOCl / TiO2 composite film
CN119771186A
Surface modification method for improving surface free energy of polyester film base for medical dry film and product thereof
CN120502478A
